Envelhecimento humano, velhice e grupos de terceira idade : a perspectiva dos facilitadores do Sesc/RS - Schmitz, Eduardo Danilo (2014)
The demographic transition is a worldwide phenomenon through which, currently , the number of older people grows so fast . In developing countries like Brazil, however, the human aging happens in the midst of social inequality . Given this scenario, the pioneer of the SESC in Brazil, through the coexistence groups, the initiative that became an alternative to supply the lack of appropriate public policies for the elderly emerged. In Rio Grande do Sul SESC maintains 45 elderly community groups in Programa SESC Maturidade Ativa. A facilitator, who has a very important role-play for the development of this project, leads each group. In this context, the first objective of this research was to understand the constructed images of aging and old age, from the perspective of these group facilitators SESC / RS. The second objective was to identify the impact on the daily lives of the elderly by the facilitators recognized as resulting from the activities carried out by groups of coexistence. To achieve these goals, this research used a qualitative approach and the focus method. Five sessions of focus groups were conduced, involving 38 facilitators of SESC / RS. The results were presented in the form of two scientific productions, each to serve a purpose of the research. The first production showed that images of human aging and old age, from the perspective of facilitators are made in two categories: positive stereotypes, in which the understanding that old age is a stage to enjoy life and also synonymous with wisdom and experience emerged and negative stereotypes, which emerged in the association of old age with illness, loss disability, limitations and pain. The second production showed that facilitators recognize that the third age group affects the lives of seniors by promoting socialization inside and outside the group, new experiences, social identification, improving self-esteem and autonomy, and support in difficult times, promoting knowledge and cognitive development, providing joy and well-being by improving health and allowing the elderly feel useful. Therefore, elderly groups were consideres by the facilitators as important strategies that contribute to a dignified old age